2016
DOI: 10.3732/ajb.1600240
|View full text |Cite
|
Sign up to set email alerts
|

Prezygotic resource‐allocation dynamics and reproductive trade‐offs in Calymperaceae (Bryophyta)

Abstract: Trade-offs among reproductive strategies and positive density-dependent senescence of female gametangia suggest that prezygotic sexual and asexual expression come at a tangible investment. However, the apparently inefficient resource-allocation dynamics in the production of female gametangia makes the possible advantages of squandering such investments unclear. One possibility is that the study populations, like those of many dioicous mosses, are skewed toward expressing females with low sporophyte production,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…30 mm in A. aculeatum and enclosure of seeds within a 10–16 cm globose, functionally indehiscent woody capsule in B. excelsa ). The strong IBD pattern revealed here is, nonetheless, consistent with the dispersal traits of the studied species, including the absence of male expression ( S. annotinus , Pereira et al ., 2016), the prevalence of dioicy in Calymperaceae associated with low sporophyte production (Pereira et al ., 2019b), the immersion of the sporophytes within perichaetial leaves or very short setae ( S. annotinus , S. helicophyllus ), and reduced peristomes ( S. annotinus , S. hornschuchii ). This strong IBD pattern is also consistent with the fact that, while bryophyte species are mostly wind‐dispersed (see Patiño & Vanderpoorten, 2018 for review), anemochorous plants in dense tropical rainforests typically exhibit tighter clusters than animal‐dispersed species because of the barriers imposed by the dense forest canopy on wind speed (Seidler & Plotkin, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…30 mm in A. aculeatum and enclosure of seeds within a 10–16 cm globose, functionally indehiscent woody capsule in B. excelsa ). The strong IBD pattern revealed here is, nonetheless, consistent with the dispersal traits of the studied species, including the absence of male expression ( S. annotinus , Pereira et al ., 2016), the prevalence of dioicy in Calymperaceae associated with low sporophyte production (Pereira et al ., 2019b), the immersion of the sporophytes within perichaetial leaves or very short setae ( S. annotinus , S. helicophyllus ), and reduced peristomes ( S. annotinus , S. hornschuchii ). This strong IBD pattern is also consistent with the fact that, while bryophyte species are mostly wind‐dispersed (see Patiño & Vanderpoorten, 2018 for review), anemochorous plants in dense tropical rainforests typically exhibit tighter clusters than animal‐dispersed species because of the barriers imposed by the dense forest canopy on wind speed (Seidler & Plotkin, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals of S. annotinus and S. simmondsii in fact grow in the close vicinity of each other, so that sperm cells may reach the archegonia of a non‐conspecific female individual. In a one‐year monitoring survey of sex expression, Pereira et al () failed, however, to find expressed males and sporophytes in S. annotinus , while expressed males and sporophytes were found in <1% and 5% of investigated individuals, respectively, in S. simmondsii . Since gametangia production was positively correlated with precipitation (Pereira et al, ), we hypothesize that interspecific gene flow reported here dates back to historical periods of increased sexual reproduction associated with historically wetter climates.…”
Section: Discussionmentioning
confidence: 98%
“…One hypothesis to explain this phenomenon is that the decline is associated with environmental depression on the energetic costs to produce reproductive organs (Fisher, 2011). As cause of restriction of sexual reproduction, environmental/geographical limits of either or both of sexes and geographical/genetic isolation between females and males have been reported (e.g., Pereira, Dambros, & Zartman, 2016; Vitasse et al., 2013). However, the environmental effects were much stronger than genetic effects on sexual reproduction parameters as phenology (Vitasse et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This may result in a best‐of‐both‐worlds reproductive strategy, where diploid spores expand in established populations and haploid spores colonize new sites. Bryophytes are ideal candidates for mating ecology studies in plants because of their haploid dominated life cycle, diverse sexual strategies, and reliance on asexual reproduction (Pereira et al., 2016). Also, they can disperse by asexual reproduction beyond the limits of sexual reproduction (Fisher, 2011; Longton, 1988).…”
Section: Introductionmentioning
confidence: 99%